Beeldverhaal & Graphic Novel 2013-2014. - Mingneau, Siska; De Ruytter, Jonas (Gent : KASK, 2014)
De Jaegher, Suzanne ; Rosseel, Pieter ; Bostyn, Korneel ; Hougardy, Eline ; Verheecke, Babette ; Verplancke, Astrid ; Dejonghe, Leen ; De Wilde, Goedele ; Van den Eynden, Lora ; Mingneau, Siska ; Camerlynck, Aaike ; Field, Jannah ; Derveaux, Lieselot ; de Vries, Katja ; De Jaeger, Ruth
boek